Prospecção química, atividade antioxidante e antimicrobiana das folhas e caules de Croton adamantinus Müll. Arg. (EUPHORBIACEAE) - Sousa, Raiane de Brito (2022)
Croton adamantinus MÜLL. ARG, also known as “carrasco” and “velame-bravo”, it is a plant used by Brazilian traditional medicine to improve the healing process and treat digestive and liver problems, however there is no study about its chemical composition neither biological activity using extract of leaves or stems. Thus, this research aimed to carry out a C. adamantinus phytochemical study and investigation on its antimicrobial and antioxidant activity. The stems and leaves’ ethanolic extracts (EEF-CA e EEC-CA) and the fractions (EEF-F2, EEF-F3, EEFF4 e EEF-F5) and (EEC-F2, EEC-F3, EEC-F4 e EEC-F5) were submitted to phytochemical screening and phytochemical analysis by Liquid chromatography coupled to Eletrospray Ionization Mass Spectrometry with “Time of Fly” type analyzer (CL-EM-ESI-TOF). The antimicrobial activity evaluation was carried out by the agar diffusion method. And the antioxidant activity was evaluated by through UV-Vis spectrophotometer by DPPH and metal chelation methods. Based on the analysis of the phytochemical screening, the presence of flavonoids, alkaloids and others was determined. This result was reaffirmed in the CL-EM-ESITOF analysis, which showed the presence of flavonoids, allowing the identification of possible compounds: isomers of apigenin 7-O-glucoside or luteolin-8-C-rhamnoside, isovitexin (apigenin 6- c-glucoside), hydroxyphenylethyl-caffeoyl glucopyranoside, nagylactone E, among others. In the in vitro study of antimicrobial activity by agar diffusion, the EEF-F1, EEFF3, EEC-F2 and EEC-F3 fractions showed zones of inhibition against S. aureus (9±0,00; 9±0,00; 9±0,00 and 9±0,00 mm) respectively, and the EEF-F2 and EEF-F3 fractions showed inhibition against E.coli (9±0,00 e 10 ±0,00 mm). As for fungal strain C.tropicali, the EEF-F1, EEF-F2 and EEC-F2 fractions were active with an inhibition of 6±0,00; 966±0,57 e 9,66±0,57 mm. Both the extracts and the polar fractions showed antioxidant potential with the tested methods. Therefore, this is the first study that reports the identification of chemical constituents for extracts of the species C. adamantinus, and it shows the importance of the dereplication method in the identification of known compounds.